Global culture : nationalism, globalisation and modernity : a theory, culture & society special issue - Featherstone, Mike (Sage, 1991)
Recent decades have seen intensified flows of people, commodities, money, ideas, information and images on a global level. Is a unified world culture emerging? And if so, how does this relate to existing cultural divisions and to the autonomy of the nation state?\In this book leading social scientists from many countries analyze the extent to which we are seeing a globalizaton of culture. Differing explanations are offered for trends towards global unification and their relation to an economic world-system. The contributors explore the emergence of `third cultures'', such as international law, the financial markets and media conglomerates, as elements which transcend the boundaries of the nation state. Will the intensification of global contact produce increasing tolerance of other cultures? Or will an integrating culture produce sharper reactions in the form of fundamentalist and nationalist movements?\As well as examining the extent, causation and consequences of global homogenization, the authors consider its implication for the social sciences. To what extent can sociology still retain the notion of the nation-state society as its basic unit?\Cultural globalization is widely perceived but as yet little analyzed. This innovative volume will appeal to a wide market in the social sciences and humanities with particular interest to teachers and students of sociology, cultural studies, anthropology and political science.